Multi-criteria decision-making method for emergency shelter site selection considering flood risk: A case study of Zhuhai, China - Bo Liu; Yingbing Li; Yan Zhang; Zhichao Wu; Yansong Pan; Meiquan Li (Cleaner Engineering and Technology)
In China, the annual area affected by floods accounts for approximately two-thirds of the total land area, causing enormous losses, particularly in developed urban areas. Therefore, establishing and improving urban emergency shelter systems has become indispensable to guarantee cities' safety and development in the new era. However, the existing site selection schemes are not comprehensive enough in the selection of influencing factors and the design of decision-making algorithms, making it difficult to cope with complex flood relief scenarios. To address these two issues, this study innovatively proposes a new multi-criteria decision-making model for selecting urban emergency shelter sites. (1) For the first time, the model systematically classifies the factors affecting the location of emergency shelter sites into four categories: hazard, exposure, vulnerability, and relief capacity, from which 11 decision-making indicators, such as flood risk, precipitation, and slope, are selected; (2) The model integrates multiple algorithms, including analytic hierarchy process, entropy weight method, Pearson's correlation coefficient, and TOPSIS, during the decision-making process, and is capable of comprehensively weighing the expert's subjective preferences, objective indicator levels and the relationship between multiple indicators to achieve a more reasonable ranking. The model was applied and evaluated in the city of Zhuhai as an example, and the results showed that more than 90% of the existing emergency shelters and natural disaster shelters in this study were located near the selected sites. In addition, the coverage rate of the selected locations in this study significantly increased by 55.3%, which exceeded the results of all comparative experiments established in this study. Among the 11 indicators involved in decision making, the most sensitive to the site selection results were slope and impervious surface, and the least sensitive was fire station accessibility. Meanwhile, we found that the central part of Xiangzhou District in Zhuhai City has the greatest demand for emergency shelter construction and the best conditions for emergency shelter construction. The flood emergency shelter site selection method proposed in this study has great potential in theory and practice, and provides a broad prospect for urban flood prevention and mitigation.